An Exploratory Study of Thriving in Latina/o Undergraduate Students in the U.S. - Morgan Consoli, Melissa L.; Llamas, Jasmin D.; Cabrera, A. Patricia; Noriega, Erika; Gonzalez, Nelly (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
Thriving, the phenomenon of going through an adversity and emerging “better off,” has been relatively understudied in the field of psychology. The current study investigated thriving in Latino/a undergraduate students. Analysis of qualitative interviews through Consensual Qualitative Research (CQR; Hill, Thompson & Williams, 1997) revealed adversities experienced (e.g., family discord and cultural difficulties), methods of thriving (e.g., cognitive coping, cultural values, faith, resources, social support and perseverance), and gains from the experience (e.g., improved self-concept, improved relationships, and increased knowledge base). Implications, limitations, and future directions are discussed.